DAMPAK TEKNOLOGI TERHADAP PSIKOLOGI MUSLIM KONTEMPORER TENTANG PENGGUNAAN MEDIA SOSIAL [THE IMPACT OF TECHNOLOGY ON CONTEMPORARY MUSLIM PSYCHOLOGY REGARDING THE USE OFSOCIAL MEDIA] - Utami, Andini Putri Wira; Fauzi, Ahmad (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2023)
Technological developments, especially social media, have provided wider access to information and communication for contemporary Muslim individuals. However, the influence of this technology also carries risks and negative impacts on Muslim psychology, including the spread of false information, social comparisons, conflicts, and addiction disorders. The study discusses the impact of technology on the psychology of individuals and Muslim communities. This article uses the literature review method to gather data from a variety of literary sources that are relevant to the research topic. Data is systematically analyzed to identify patterns, findings, and latest developments related to the impact of technology, especially social media, on the psychology of Muslim individuals. The use of social media has enriched the knowledge of Muslim individuals about religion and enabled inter-Muslim interactions around the world. However, risks such as the spread of false information, social comparisons, and addiction disorders also affect their psychology. Education, critical skills development, psychological support, wise time management, and inter-Muslim dialogue can help overcome the negative impact. The influence of technology on contemporary Muslim psychology involves complex aspects. Education and awareness of the risks associated with social media are essential to addressing its negative impact. In addition, good time management, effective communication, and attention to religious practices and Islamic values must also be taken into account.